About Turkic component in world culture and civilization - Булекбаев, Сагади (Eurasian Journal of Religious Studies, 2017)
In this article, the authors, based on the research of outstanding scientists in Turkic studies, open a huge contribution of Turkic peoples into the world culture and civilization which had not only a huge impact, but also set starting conditions for development of other civilizations, first of all the European.